2023
DOI: 10.1021/acs.jpclett.3c00142
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Ground-State Electronic Structure from Core-Loss Spectra of Organic Molecules by Machine Learning

Abstract: The core-loss spectrum reflects the partial density of states (PDOS) of the unoccupied states at the excited state and is a powerful analytical technique to investigate local atomic and electronic structures of materials. However, various molecular properties governed by the ground-state electronic structure of the occupied orbital cannot be directly obtained from the core-loss spectra. Here, we constructed a machine learning model to predict the groundstate carbon s-and p-orbital PDOS in both occupied and uno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…17−25 Furthermore, it has recently been reported that it is possible to predict the electronic structure of organic molecules in their ground state from C-K edge ELNES/XANES. 26 Building upon prior research employing ML methods, we aim to develop an ML-model to predict the atom-specific electronic structure of all orbitals in their ground state for solid materials from ELNES/XANES, toward the realization of atomic-level analysis of ground-state electronic structures. In this study, we focus on the Si-K edge of Si.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17−25 Furthermore, it has recently been reported that it is possible to predict the electronic structure of organic molecules in their ground state from C-K edge ELNES/XANES. 26 Building upon prior research employing ML methods, we aim to develop an ML-model to predict the atom-specific electronic structure of all orbitals in their ground state for solid materials from ELNES/XANES, toward the realization of atomic-level analysis of ground-state electronic structures. In this study, we focus on the Si-K edge of Si.…”
Section: ■ Introductionmentioning
confidence: 99%
“…On the other hand, in recent years, the effectiveness of employing ML techniques in materials characterization has been demonstrated . ML has also increasingly been utilized in extracting information from ELNES/XANES spectra, with methods reported for directly predicting atomic structure and material properties from ELNES/XANES. Furthermore, it has recently been reported that it is possible to predict the electronic structure of organic molecules in their ground state from C- K edge ELNES/XANES …”
Section: Introductionmentioning
confidence: 99%
“…developed a transition metal interconnected neural network (TMINN), effectively capturing the correlation between material geometric configuration and magnetic anisotropy energy for two-dimensional meta–organic framework (MOF) materials . A feedforward neural network was successfully utilized for predicting the electronic structure of organic molecules . Moreover, multilayer deep neural networks have shown promise in simultaneously predicting molecular properties, including energy gap, electronic spatial extent, and dipole moment .…”
mentioning
confidence: 99%
“…26 A feedforward neural network was successfully utilized for predicting the electronic structure of organic molecules. 27 Moreover, multilayer deep neural networks have shown promise in simultaneously predicting molecular properties, including energy gap, electronic spatial extent, and dipole moment. 28 However, defining a universally applicable ML model for materials design poses significant challenges.…”
mentioning
confidence: 99%
See 1 more Smart Citation